Human Resource Factors in Career Satisfaction: The Role of Technology Support, Digital Self-Efficacy, and Perceived Employability with Islamic Work Ethics as a Moderating Variable - Hero Gefthi Firnando; Cucu Setiawati (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2026)
The rapid development of digital technology has transformed workplace dynamics, requiring employees to possess not only technical skills but also the ability to manage their careers independently. However, career satisfaction is not always achieved despite high levels of digital self-efficacy. This study aims to examine the effects of perceived technology support and digital self-efficacy on career satisfaction, with perceived employability as a mediating variable and Islamic Work Ethics as a moderating variable. This research employs a quantitative approach using a survey method involving 230 employees. Data were collected through questionnaires and analyzed using SmartPLS 4.0. The findings reveal that perceived technology support has a positive and significant effect on career satisfaction, while digital self-efficacy does not have a direct effect. However, both variables significantly influence perceived employability, which in turn enhances career satisfaction. Furthermore, Islamic Work Ethics strengthens the relationship between perceived employability and career satisfaction, indicating that Islamic values play a crucial role in enhancing the meaning and fulfillment of careers. This study concludes that integrating organizational support, individual capabilities, and Islamic work ethics is essential in fostering sustainable career satisfaction